Secondary Control Reviewed and Defined. [article]. - Morling, Beth
Conclusions about secondary control have been hindered by researchers' disperate interpretations of the construct. The current review offers the definition that reflects commonality among researchers and the spirit of the original article. (F. Rothbaum, J. R. Weisz, & S. S. snyder, 1982); Secondary control refers to the process by which people adjust some aspect of the self and accept circumstances as thet are. The authors also identify a "fit versus control" dimension along with secondary control research can be classified and reviewed. The authors conclude that fif-focused secondary control. is adaptive and coping, is relatively preferred in interdependent cultural context, and may serve the motivation for relatedness. Control-focused leads to different interpretations of the function and cultural nature of secondary control. The proposed definition and dimension should enable researchers to articulate assumptions about the function and correlates the secondary control. -- (from the author)